The behavior of solutions of the mixed boundary value problem for a linear second-order elliptic equation in a neighbourhood of intersecting edges - Plesha, M. (Інститут прикладної математики і механіки НАН України, 2008)
In this paper we deals with the mixed boundary value problem for secondorder elliptic equations in a polyhedral domain. We obtain exact estimates for solutions of the problem in a neighbourhood of an vertex. A special section is dedicated to the examples.